2015
DOI: 10.1002/lt.24303
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of the nuclear factor (erythroid‐derived 2)–like 2–antioxidant response element pathway in hepatocytes decreases hepatic ischemia/reperfusion injury in mice

Abstract: Background and Aims Hepatic ischemia reperfusion injury (IRI) is a critical component of hepatic surgery. Oxidative stress has long been implicated as a key player in IRI. In this study, we examine the cell-specific role of the Nrf2-antioxidant response element pathway in warm hepatic IRI. Methods Nrf2 KO and WT animals, and novel transgenic mice expressing a constitutively active Nrf2 mutant in hepatocytes (AlbCre+/caNrf2+) and their littermate controls underwent partial hepatic ischemia or sham surgery. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…A recent study demonstrated that transgenic overexpression of Nrf2 in hepatocytes of lean donor livers can protect those livers from hepatocellular damage sustained after liver transplantation . We have recently shown that overactivation of Nrf2 in hepatocytes leads to reduced cellular damage after IRI . However, the study described here is the first to look at the role of direct, cell‐specific overactivation of Nrf2 in nonparenchymal cells in a model of warm hepatic IRI.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…A recent study demonstrated that transgenic overexpression of Nrf2 in hepatocytes of lean donor livers can protect those livers from hepatocellular damage sustained after liver transplantation . We have recently shown that overactivation of Nrf2 in hepatocytes leads to reduced cellular damage after IRI . However, the study described here is the first to look at the role of direct, cell‐specific overactivation of Nrf2 in nonparenchymal cells in a model of warm hepatic IRI.…”
Section: Discussionmentioning
confidence: 88%
“…(11) We have recently shown that overactivation of Nrf2 in hepatocytes leads to reduced cellular damage after IRI. (10) However, the study described here is the first to look at the role of direct, cell-specific overactivation of Nrf2 in nonparenchymal cells in a model of warm hepatic IRI. By using novel transgenic mice, we intended to more precisely decipher the cell-specific role of Nrf2 in hepatic IRI.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations